Pelayanan Administrasi Kependudukan Masyarakat Desa Gemalasari Kabupaten Kepulauan Meranti Berbasis Android - Abza, Adhamdi Tria Putra (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
The village office has various tasks related to government, empowerment, development and guidance in the village. At the Village Office, various services are provided such as processing certificates, processing death certificates, and various other administrative services. The Gemalasari Village Office is also the center of village government, where various village government activities are carried out. for example, applying for KTP, making marriage certificates, making birth and death certificates, as well as distributing government programs. Apart from that, the village office can also be a place for marriage registration. This research aims to make it easier for village officials to manage required administrative correspondence using only smartphones.